Enteral Nutrition in Intensive Care: 'Tiger Tube'-For Small Bowel Feeding in Acute Pancreatitis. Case Report. - Mat Nor, Mohd Basri (International Islamic University Malaysia, 2007)
Nutritional support is vital in improving the clinical outcomes of the critically ill patients. Almost all published guidelines regarding nutritional support in the critically ill recommend the use of enteral nutrition over parenteral nutrition. In acute pancreatitis, trial of enteral feeding should be given into the small bowel. The success rate of small bowel feeding tube is highest if inserted endoscopically. In this case report, a simple bedside procedure which did not require endoscopic feeding tube placement offered a good alternative. Self advancing small bowel feeding tube, Tiger tube was inserted successfully to provide nutritional support in moderately severe acute pancreatitis.